An Optimization of Particle Size and Additives of Slip Cast Alumina Samples to Reduce Warpage and Porosity - V. Sivamaran; V. Kavimani; M. Bakkiyaraj; C. Rajendran; Tushar Sonar (Advances in Materials Science and Engineering)
Alumina body densification using slip casting was investigated with low warpage rates. In order to optimize slurry and sintering, 1600°C has been used. As a starting material, three types of alumina were used. Alumina has been used in conjunction with PMAA, and carboxymethyl cellulose in order to prepare the slurry. It was found that warpage rates were reduced when coarser particles were included in the composition. An acid treatment of the slurry was carried out in order to improve densification of the alumina body and to reduce warpage. This study examines the microstructure of a sintered alumina body. In the investigation, it was found that preparing a dense product reduced porosity and warping rate by 1.1% and 4%, respectively.